Kondo-like electronic transport and ferromagnetic cluster-glass behavior in La0.7Sr0.3MnO3 nanostructures. Issue 104 (11th November 2015) - Reshi, Hilal Ahmad; Pillai, Shreeja; Yadav, Rama Shanker; Para, Touseef Ahmad; Deshpande, U. P.; Shripathi, T.; Shelke, Vilas
<x xml:space="preserve">Abstract</x> We have studied the electronic transport and magnetic properties of a nanocrystalline La0.7Sr0.3MnO3 system. We observed low temperature Kondo effect with magnetic cluster behavior.